UMTS - Sanchez, Javier (ISTE Ltd., 2007)
During the first decade of this new millennium, it is estimated that more than €100 billion will be invested in the third generation (3G) Universal Mobile Telecommunications System (UMTS) in Europe. This fact represents an amazing challenge from both a technical and commercial perspective. Written by experts in the field, this book gives a detailed description of the elements in the UMTS network architecture: the User Equipment (UE), the UMTS Radio Access Network (UTRAN) and the core network. The completely new protocols based on the needs of the new Wideband Code Division Multiple Access (WCDMA) air interface are highlighted by considering both Frequency- and Time-Division Duplex modes. The book further introduces the key features of existing topics in Releases 5, 6 and 7.